Experimental Investigation on Flexural Behavior of Granite Stone Slabs with Near Surface Mounted CFRP Bars and Screw-Thread Steels - Xiaopeng Gao; Zhongfan Chen; Xiaomeng Ding; Erxiang Dong (Advances in Materials Science and Engineering)
An experimental study that investigates the behavior of stone slabs strengthened in fixure with near surface mounted (NSM) technique using screw-thread steels and carbon fiber-reinforced polymer (CFRP) bars is presented. A total of ten full-scale stone slabs were tested under a four-point bending loading to investigate the effect of groove dimension, reinforcement ratios, and reinforcement materials on the flexural performance of stone slabs. The test results included failure characteristics, yield and ultimate capacities, deflection of midspan, and cracking behavior of stone slabs. The test results indicate that with the increase of groove height and groove width, cracking load and middeflection decrease by 6.4%–14.18%; however, failure load and middeflection increase by 4.7%–41.2%. Cracking load, failure load, and failure displacement of stone slabs adopting NSM screw-thread steels increased by 10.9%, 167%, and 617%, respectively, under the maximum reinforcement ratios of 0.629% over the control slab without NSM bars. Meanwhile, with the increase of reinforcement ratios, the failure mode transforms from brittle failure to ductile failure. The calculation results of strength are in agreement with the experimental results. Finally, it can be concluded that NSM CFRP bars are more effective than NSM screw-thread steels to improve flexural capacity with the same reinforcement ratios.